Common alpha globin deletion mutation spectrum in hemoglobin H disease patients in the Mekong Delta, Vietnam - Vo , Thanh Tri; Le , Thi Hoang My; Trinh , Thi Hong Cua; Pham, Thi Ngoc Nga; Tran, Phuoc Thinh; Phan, Hoang Dat, B.Sc.; Nguyen, Phuc Duc; Nguyen, Chi Nguyen; Vo, Thai Duong (Asian Medical Journal and Alternative Medicine, 2023)
Introduction: Hemoglobin H disease is a type of α-thalassemia brought on by a shortage in the generation of hemoglobin globin chains (Hb). The patients produce a form of hemoglobin called hemoglobin H by inactivation of three α-globin genes. In this paper, we report the presence of the four deletion mutations of Southeast Asia in hemoglobin H disease patients in the Mekong Delta, Vietnam. Methods: DNA from 50 hemoglobin H disease patients were extracted from EDTA-anticoagulated whole blood and screened for the four common α-globin deletion mutations using Gap-Polymerase Chain Reaction. Results: The most common type of deletion was –SEA deletion, accounting for 73.5% of the mutant alleles, followed by the -α3.7 (rightward) deletion (19.1%) and -α4.2 (leftward) deletion (7.4%) mutation in this region. In this study, the –THAI mutation was not detected. Conclusions: This study gave an overview of the prevalence of typical α-globin gene mutations in Vietnam and might act as a starting point for a further research into these genetic flaws.